Characterization and in vitro translation of polyadenylated messenger ribonucleic acid from Neurospora crassa. - Lucas, M C (1977)
Ribonucleic acid (RNA) extracted from Neurospora crassa has been fractionated by oligodeoxythymidylic acid [oligo(dT)]-cellulose chromatography into polyadenylated messenger RNA [poly(A) mRNA] and unbound RNA. The poly(A) mRNA, which comprises approximately 1.7% of the total cellular RNA, was further characterized by Sepharose 4B chromatography and polyacrylamide gel electrophoresis. Both techniques showed that the poly(A) mRNA was heterodisperse in size, with an average molecular weight similar to that of 17S ribosomal RNA (rRNA). The poly(A) segments isolated from the poly(A) mRNA were relatively short, with three major size classes of 30, 55, and 70 nucleotides. Gel electrophoresis of the non-poly(A) RNA indicated that it contained primarily rRNA and 4S RNA. The optimal conditions were determined for the translation of Neurospora mRNA in a cell-free wheat germ protein-synthesizing system. Poly(A) mRNA stimulated the incorporation of [14C]leucine into polypeptides ranging in size from 10,000 to 100,000 daltons. The RNA that did not bind to oligo(dT)-cellulose also stimulated the incorporation of [14C]leucine, indicating that this fraction contains a significant concentration of mRNA which has either no poly(A) or very short poly(A) segments. In addition, the translation of both poly(A) mRNA and unbound mRNA was inhibited by 7-methylguanosine-5'-monophosphate (m7G5'p). This is preliminary evidence for the existence of a 5'-RNA "cap" on Neurospora mRNA.